2020
DOI: 10.1021/acsami.0c05158
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Nanocomposite of AgBr in g-C3N4Matrix Exhibiting Efficient Antibacterial Effect on Drought-ResistantPseudomonas putidaunder Dark and Light Conditions

Abstract: Synthesis of nanocomposites possessing intimately mixed components is highly challenging to bring out the best possible properties of the materials. The challenge is mainly due to the difficulties associated with controlling the phase segregation of individual components as a result of high interfacial tension between them and cohesive forces within each component during the synthesis. Here, we show a single-step synthesis of representative nanocomposites of g-C 3 N 4 /AgBr through a rationally designed approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 70 publications
(88 reference statements)
3
27
0
Order By: Relevance
“…The small shoulder peak arising at 285.56 eV can be attributed to C-O bond which could be from the adsorbed oxygen on the surface of h-BN. 53 The most dominant peak for boron is ∼ 190.56 eV which is very close to the ideal value of boron position in hexagonal boron nitride. 54 This peak corresponds to the B-N bond in h-BN.…”
Section: Methodssupporting
confidence: 56%
“…The small shoulder peak arising at 285.56 eV can be attributed to C-O bond which could be from the adsorbed oxygen on the surface of h-BN. 53 The most dominant peak for boron is ∼ 190.56 eV which is very close to the ideal value of boron position in hexagonal boron nitride. 54 This peak corresponds to the B-N bond in h-BN.…”
Section: Methodssupporting
confidence: 56%
“…Survey spectra in Figure a show the existence of Nb, O, and F elements in NOF/CN-0.1 samples, C and N elements in CN samples, and C, N, Nb, O, and F elements in the NOF/CN-0.1 sample, which is well in agreement with XRD and EDS results. As illustrated in Figure b, narrow-scanned C 1s spectra in CN nanosheets and NOF/CN-0.1 composites indicate that the peaks at 284.8, 286.3, 288.3, and 289.3 eV can be assigned to C–C, C–N–C, N–CN, and O–CO, respectively. , In Figure c, the peaks at 398.7, 399.8, and 400.8 eV in the narrow-scanned N 1s spectra can be indexed to C–NC, N–(C) 3 , and C–NH, respectively . From narrow-scanned Nb 3d spectra in NOF/CN-0.1 hybrids (Figure d), it can be found that binding energy shifts to a lower position with 0.2–0.3 eV compared to pure NOF, indicating the strong interaction or the formation of a heterojunction between the two components.…”
Section: Results and Discussionmentioning
confidence: 89%
“…25,26 In Figure 5c, the peaks at 398.7, 399.8, and 400.8 eV in the narrow-scanned N 1s spectra can be indexed to C−NC, N− (C) 3 , and C−NH, respectively. 27 From narrow-scanned Nb 3d spectra in NOF/CN-0.1 hybrids (Figure 5d), it can be found that binding energy shifts to a lower position with 0.2−0.3 eV compared to pure NOF, indicating the strong interaction or the formation of a heterojunction between the two components. In Figure 5e, the peaks at 530.1 and 531.8 eV can be ascribed to lattice oxygen and adsorbed oxygen.…”
Section: Resultsmentioning
confidence: 96%
“…In the 3‐Ag/g‐C 3 N 4 material prepared by Wei et al., [21] the hydrogen ions at the valence band of g‐C 3 N 4 plays a leading role in the photocatalytic disinfection of Escherichia coli and nanosilver particles suppress the recombination of photogenerated electrons and hydrogen ions, and further enhancing the photocatalytic performance of g‐C 3 N 4 . Balapure et al [22] . synthesized g‐C 3 N 4 /AgBr nanocomposites in the materials containing silver halide.…”
Section: Synthesis Of G‐c3n4 and Its Compositesmentioning
confidence: 99%